Tropical application of floating treatment wetlands - Weragoda, S. K. (2013)
The treatment efficiencies of floating treatment wetlands (FTWs) containing two types of macrophytes, Typha angustifolia and Canna iridiflora, were investigated in a pilot scale study in the tropical climate of Sri Lanka. In batch experiments, over 80 % of biological oxygen demand (BOD5) and ammonium (NH 4 +-N) removal was observed, while nitrate (NO 3 −-N) removal was over 40 %. Typha angustifolia showed slightly higher BOD5, NH 4 +-N and NO 3 −-N removal than Canna iridiflora. Because of higher and steady root growth, Typha angustifolia resulted in a better performance and has a greater potential to extract nutrients from wastewater and allow water-plant interactions than Canna iridiflora whose root mat is thick and compact. Similar to the batch system, the continuous flow systems performed better at most times with Typha angustifolia. FTWs with Typha angustifolia may be considered a possible solution for lake restoration where there are space and cost constraints.